Economic Nature of A. Yu. Simanovskiy Crypto-Currency - Т. S. Novashina (Вестник Российского экономического университета имени Г. В. Плеханова)
The author by analyzing theoretical ideas put forward b y A. Yu. Simanovskiy in the research ‘Concerning Economic Nature of Crypto-Currency’, which was published in the journal “Issues of Economics’ provides his own opinion concerning whether currency (including crypto-currency) can have economic nature. This question is not rhetoric and has nothing to do with casuistry. It is essential, principle and touches upon problems dealing with national security. On the basis of system-functional analysis and achievements of modern theory of money and using its fundamental provisions the author considers the content of money in dialectic unity of form transformation (material, money, paper, electronic) and spheres (social – money as a symbol; economic – bank notes; political and legal – monetary units) of their being. It is shown that currency, especially crypto-currency cannot have economic nature. In this connection the author studying the process of historical transformation of international monetary systems with regard to achievements of finance, technical and social engineering aimed at creation of ‘digital gold’ thinks that the social and economic model of the future international monetary system has been tested already.